Trajectories of plasma Aβ42/40 among African Americans: Preliminary results from the African American Fighting Alzheimer's in Midlife (AA‐FAIM) study. (20th December 2022) - Van Hulle, Carol A.; Zuelsdorff, Megan; Koscik, Rebecca Langhough; Ennis, Gilda E.; Bouges, Shenikqua; Fischer, Barbara L.; Wyman, Mary F.; Lambrou, Nickolas H.; Johnson, Adrienne L.; Umucu, Emre; Salazar, Hector; Chin, Nathaniel A.; et al.
Abstract: Background: African Americans (AA) are under‐represented in Alzheimer's disease (AD) biomarker research. Blood‐based biomarkers for AD offer the promise of greater diversity in research studies, but little is known about the performance of these biomarkers within an AA cohort. We examined the association between modifiable and non‐modifiable risk factors on the trajectory of plasma measures of Aβ42/40 in a large well‐characterized AA cohort. Method: N =318 AA participants enrolled in in African Americans Fighting Alzheimer's in Mid‐Life (AA‐FAIM) provided 690 plasma samples. The ratio Ab42/40 was calculated from plasma Aβ40 and Aβ42 quantified by C2N Diagnostics (PrecivityAD™; Figure 1). Age range was 39 ‐ 87 years at baseline (see Table 1); 52% of the cohort provided ≥2 plasma samples. Mixed‐effects linear models were used to test for longitudinal change in Aβ42/40 where years since baseline was the measure of time ( M = 4.13 years, range = 1 to 16 years). To determine if risk factors modified Aβ42/40 trajectory, we tested the interactions between time and the following AD risk factors: APOE genetic risk, cardiovascular factors measured at baseline plasma sample (blood pressure, BMI, total cholesterol), and amyloid PET positivity. Result: Raw Aβ42/40 values plotted against time are shown in Figure 2. None of the risk factors modified the trajectory of Aβ42/40 ( p values ranged .22 to .84), which declined by approximately 1% per year over baseline ( p <.001; Table 2). After accounting for longitudinal trajectory, Ab42/40 was 3% lower among APOE ε4 carriers, while higher baseline total cholesterol was associated with higher Aβ42/40 . In a subset of participants with PiB‐PET visual ratings ( N =35), amyloid positive participants (N=10) had 12% lower plasma Aβ42/40 values than amyloid negative participants ( p <.001) after accounting for longitudinal trajectory. Conclusion: These initial analyses conducted exclusively in African Americans suggest that clinical risk factors (total cholesterol, APOE ) can influence brain amyloid pathology, as determined using plasma Aβ42/40 . More research is needed to fully characterize AD pathology and dementia risk in AAs. This research is imperative in light of the disproportionate burden of dementia in the AA community and the increasing use of biomarkers in research and clinical practice.